Pantoea eucrina: Catheter‐Related Bloodstream Infection in a Woman With Short Bowel Syndrome - Ida Saksenborg Kølle; Lars Vinter‐Jensen; Morten Eneberg Nielsen; Hans Linde Nielsen (Clinical Case Reports)
ABSTRACT Pantoea eucrina, a member of the Erwiniaceae family, is a rarely reported human pathogen primarily associated with plants. This study presents a documented case of catheter‐related bloodstream infection caused by P. eucrina in a 60‐year‐old female receiving home parenteral nutrition. Despite presenting with only minor clinical symptoms, blood cultures from both central and peripheral sites confirmed the presence of P. eucrina, identified by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) and whole‐genome sequencing. The infection was successfully cleared following a 13‐day course of gentamicin lock therapy and intravenous piperacillin–tazobactam, after which the catheter was removed.